Feasibility of a monetary union in east African community / Kamaladin Ahmed Sheikh - Sheikh, Kamaladin Ahmed (2014)
In recent years, the pursuit and interest of monetary union has become important phenomenon of economic development. Many countries in the world have the incentive to form monetary union with the intention of enjoying the benefits of increased economic integration and to avoid the monetary domination of larger countries. East African Community (EAC) like other regional economic blocs is interested to form monetary union in order to access wider market and reinforced growth, which subsequently results in higher level of economic welfare. EAC consists of five neighbouring countries, situated in the eastern part of Africa and they are Burundi, Kenya, Rwanda, Tanzania and Uganda. So far, these countries have made considerable achievements towards the formation of monetary union as they had established a Customs Union in the 2005 and Common Market in the 2010, these achievements allow free movement of goods, services, capital and labour in the block. The aim of this thesis was to assess the suitability of a monetary union among the five EAC member countries in the light of optimum currency area criteria (OCA) theory. The study reviewed and discussed the socio-economic background and the macroeconomic characteristics of the EAC member countries. Similarly, the study reviewed the literature and theoretical foundations of OCA theory and its related empirical studies. For the methodological part, this study mainly emphasises on the economic elements of a monetary union using two major econometric methods to analyze the feasibility of monetary union in EAC countries. First, a four-variable structural vector auto-regression (SVAR) model was used to identify four types of shocks: global supply shock, domestic supply shock, monetary supply shock, and domestic demand shocks; then we measure the symmetry and asymmetry of these shocks using simple correlation analysis, impulse response analysis, variance decomposition analysis, and lastly one-way Anova analysis. The second method used was business cycle synchronization analysis of HP (Hodrick-Prescott) and the BP (band pass) filters. After identifying the cycles and trends, the study applied cross country correlation analysis and analysis of variance technique to examine whether EAC countries are characterized by synchronized business cycles or not. The findings of the study did not show strong support for the formation of a currency union in the region at present, but nevertheless it gave some hope to a successful monetary union in the future. The study found that both the degree of symmetric shocks and business cycle synchronization in the EAC bloc had increased significantly for the last ten years. On the other hand, the correlation of shock analysis revealed that domestic demand shocks and external supply shocks were dominant in the region, while domestic supply shocks and monetary shocks were less correlated and asymmetry in the region. For the business cycle analysis, the results showed that EAC countries are similar in cycle components but do differ in permanent components especially in growth trend. Most of the study results were in line with previous studies. In conclusion, iv single currency for this region is an excellent idea and is believed to be an achievable target; but before that EAC countries need to implement rigorous policy co-ordination in order to achieve the desired level of symmetry of shocks and business cycle synchronization.